Aspects of the recovery program in a patient with incomplete cervical vertebro-medullary traumatism due to secondary generalized convulsive seizures - Simona Isabelle Stoica; Carmen Elena Chipăruş; Magdalena Vasilica Lăpădat; Gelu Onose (Romanian Medical Journal, 2017)
The number of spinal cord injury patients continues to be a challenge for neuromotor recovery. Consequences are sensitivity and motility disorders which leads to different invalidity degrees. At the same time, food excesses/of nutritional toxic products or other aggresive factors (urinary tract infections, ingrown nails, autonomic dysreflexia and so on) can disturb central nervous system functions up to secundar generalized scizures trrigering (which can severly affect the lifestyle of patients). For all these reasons, is very important to study carefully the evolution of spinal cord injury patients and their lifestyle precursor traumatic events. The autors will prezent the complex and difficult evolution of a case with incomplete posttraumatic tetraplegia (treated neurosurgical conservately).